2015
DOI: 10.1177/000313481508100225
|View full text |Cite
|
Sign up to set email alerts
|

Does Immediate Tissue Expander Placement Increase Immediate Postoperative Complications in Patients with Breast Cancer?

Abstract: The objectives of this study were to evaluate 1) the rate of immediate breast reconstruction; 2) the frequency of immediate tissue expander placement; and 3) to compare perioperative outcomes in patients who underwent breast reconstruction after mastectomy for breast cancer with immediate tissue expander placement (TE) with those with no reconstruction (NR). Using the Nationwide Inpatient Sample database, we examined the clinical data of patients with breast cancer who underwent mastectomy with or without imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…16 With respect to reconstructive timing, immediate TE placement is not shown to increase postoperative complications compared with no reconstruction. 17 In a large review of nipple-sparing mastectomy patients, immediate TE placement is shown to have less mastectomy flap complications compared with immediate implant or autologous-based reconstruction. 18 In our practice, many patients are offered delayed-immediate reconstruction, with rare conversion to delayed reconstruction based on the intraoperative examination of the mastectomy flaps.…”
Section: Discussionmentioning
confidence: 99%
“…16 With respect to reconstructive timing, immediate TE placement is not shown to increase postoperative complications compared with no reconstruction. 17 In a large review of nipple-sparing mastectomy patients, immediate TE placement is shown to have less mastectomy flap complications compared with immediate implant or autologous-based reconstruction. 18 In our practice, many patients are offered delayed-immediate reconstruction, with rare conversion to delayed reconstruction based on the intraoperative examination of the mastectomy flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates following immediate breast reconstruction in IBC patients appear comparable with those in non-IBC patients [39][40][41]. Notably, Hoffman et al found no difference in 30-and 90-day mortality and 30-day readmission rates between immediate reconstruction and no reconstruction [19], suggesting that for select patients, mastectomy with immediate reconstruction is a feasible procedure with minimal impact on short-term surgical morbidity and mortality [42,43]. There was no clinically significant difference in time to post-mastectomy radiotherapy (PMRT) between the breast reconstruction and no-reconstruction groups, although the data is limited.…”
Section: Discussionmentioning
confidence: 97%
“… 7 8 9 10 Among the different types of breast reconstruction, implant-based surgery is the most common option. 1 2 11 Several studies 12 13 14 15 have already demonstrated that this type of reconstruction is not associated with a negative impact on the oncologic results of breast cancer treatment, or with an increased risk of developing postoperative complications when compared with mastectomy alone.…”
Section: Introductionmentioning
confidence: 99%